Pengembangan Kreativitas Guru: Seminar Online Dalam Meningkatan Pengetahuan Tentang Penyusunan Soal Berbasis HOTs - Surjanti, Jun; Soesatyo, Yoyok; Sakti, Norida Canda; Fitrayati, Dhiah; Nurlaili, Eka Indah (Jurnal Pendidikan Ekonomi Undiksha, 2022)
The life of the 21st century requires creativity to answer the challenges of life's problems. Thus, teachers need cultivate creative students who are very supportive of life which is manifested in the behavior, knowledge, and skills shown through creativity. Teachers are encouraged to cultivate Higher-order Thinking (HOTS) in students in learning activities, not least in learning economics. The HOTS-based learning model must be followed by an HOT-based evaluation as well. However, in reality many teachers still have not applied this model in their teaching activities or still refer to the conventional model. In an effort to improve the quality of teachers, various efforts have been made, one of which is through online seminars. This research is a descriptive study with a percentage to analyze the data obtained. This activity-based research is intended to see the effect of online seminar activities in increasing teacher knowledge to develop HOTS-based questions. This activity was attended by 204 economics teachers as the object of the activity. Data was obtained through questionnaires and documentation using the Google-form platform. The results of data analysis show that online seminar activities are proven to improve teacher understanding in preparing HOTS-based questions.